2006
DOI: 10.1538/expanim.55.467
|View full text |Cite
|
Sign up to set email alerts
|

Change in Ucp1 mRNA Expression Following Long-Term Cold Exposure under Normal or High-Fat Diet Regimes in the Cold-Intolerant Mammal, Suncus murinus

Abstract: The house musk shrew (Suncus murinus), or suncus, is a unique experimental mammal that is cold intolerant. However, even basic knowledge of brown adipose tissue (BAT), which is important for non-shivering thermogenesis (NST), is minimal. Therefore, we exposed suncus for 18 days to mild cold temperatures (8-14°C) and/or a high-fat diet, which are factors that increase NST, and measured two mRNAs that are critical for NST in BAT, uncoupling protein 1 (Ucp1) and type II 5 ' -deiodinase (D2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In general, Ucp1 expression is strongly regulated by the sympathetic nervous system. The weak increase of Ucp1 was likely caused by suppression of the sympathetic nervous activity in BAT by a high-protein and low-fat diet, as in our previous study [36].…”
Section: Cold Exposure Of Up To 12 Hsupporting
confidence: 70%
See 2 more Smart Citations
“…In general, Ucp1 expression is strongly regulated by the sympathetic nervous system. The weak increase of Ucp1 was likely caused by suppression of the sympathetic nervous activity in BAT by a high-protein and low-fat diet, as in our previous study [36].…”
Section: Cold Exposure Of Up To 12 Hsupporting
confidence: 70%
“…6a, b). Because longterm exposure (18 d) to mild cold (8.5-14.6°C) with standard trout pellets did not lead to augmented Ucp1 expression levels [36], we conclude that Ucp1 up-regulation in suncus eating standard trout pellets only occurs immediately after cold exposure. Ucp1 expression in suncus may decline to normal levels after the initial increase, as it does in hamsters [45].…”
Section: Cold Exposure Of Up To 12 Hmentioning
confidence: 68%
See 1 more Smart Citation
“…Comparable data are reported for the house shrew (69). Notably, different mouse strains were employed in the two contradicting mouse studies above, and others have already demonstrated a diverging response of different strains to HFD at 5°C (12).…”
Section: Treatment Parametersmentioning
confidence: 78%
“…Twenty-three employed the mouse as an animal model (1, 3-5, 11, 15-17, 25, 32, 33, 40, 44, 49, 52, 53, 57, 63, 67, 74, 75, 78, 79), 16 employed the rat (6,23,35,38,42,43,48,58,70,71,73,77,80,82,84,85) and one used the Brandt's vole (86) and the house shrew (69), respectively. Whenever possible, we compared both the regulatory effect of a given parameter across different studies and within the same study.…”
Section: Ucp1 In Brown Adipose Tissuementioning
confidence: 99%